Brushless Direct Current Electric Motor Design with Minimum Cogging Torque - Muhammad Nizam; Hery Tri Waloyo; Inayati . (IAES Indonesia Section, 2014)
Cogging torque is one of the factors that influence electric motor efficiency. Many methods have been used to reduce the cogging torque. One of the methods is the determination of the number of slots and poles fraction. This study was intended to determine the number of slots and poles fraction to get a minimum of cogging torque. Research was done by ANSYS software. By varying the number of slots and poles, the data cogging torque and torque ripple were observed. It was found that the lesser difference between the number of slots and poles produced lower cogging torque. More numbers of slots would reduce the cogging torque. The smallest cogging torque was produced at difference in the number of slots and poles of 1 and 2. For slots more than four, the cogging torque produced were irregular.